BENZAMIDE DERIVATIVES AS POTENTIAL CANDIDATES FOR ANTI-ALZHEIMER, ANTI-FATIGUE, ANTI-UREASE AND ANTI-OXIDANT ACTIVITY - Taj, M. B.; Tirmizi, S. A.; Raheel, A.; Ali, H. B. M.; Qureshi, S.; Alshatir, H. (Journal of the Chilean Chemical Society, 2017)
Benzamide derivatives were screened for their anti-alzheimer, anti-fatigue, anti-urease and anti-oxidant activity and their results were calculated in the form of %age inhibition and IC50 value. Compounds 3a and 3g exhibited the highest anti alzheimer activity. Group of mice’s treated by compounds 3f and 3g showed significantly longer swimming times than those of the treated with caffeine. The prominent urease inhibitory activity was shown by only one compound among seven benzamide derivatives. Controlled experiments suggest that benzamide derivatives (3a-3g) can be serve as the therapeutic agents.